COMPARISON OF PROGNOSTIC ACCURACIES OF HEMATOLOGICAL SCORING SYSTEMS FOR DETERMINING MAJOR MOLECULAR RESPONSE IN NEWLY DIAGNOSED PATIENTS OF CHRONIC MYELOID LEUKEMIA IN CHRONIC PHASE (The Research of Medical Science Review, 2025)
Objective: To determine frequency of Major Molecular Response in newly diagnosed patients of chronic myeloid leukemia (CML) in chronic phase undergoing treatment with Imatinib based on various scoring systems. Materials and Methods: A total of 150 newly Diagnosed BCR-ABL POSITIVE CML patients in chronic phase receiving imatinib were included in this case series. The patient were recruited from the department of hematology, Holy Family Hospital Rawalpindi. The study was conducted from 11-May-2022 to 10-February-2025. Before starting treatment for CML, platelet count, blast cells percentage, eosinophils percentage and basophils percentage was determined. Clinical examination was done to assess the spleen size. Reports were assessed, and all the scores such as Sokal, Hasford, EUTOS and ELTS were calculated. Results: Mean age of patients was 44.16±12.63 years. There were 90 (60%) male and 60 (40%) female patients. On comparison of prognostic accuracies of haematological scoring for MMR, 57 (82.6%) patients with low Sokal score achieved MMR, 30 (63.8%) patients with intermediate Sokal score achieved MMR and 12 (35.3%) patients with high Sokal score achieved MMR with pvalue of <0.001. There were 38 (88.4%) patients with low Hasford score achieved MMR, 52 (63.4%) patients with intermediate Hasford score achieved MMR and 09 (36.0%) patients with high Hasford score achieved MMR with p value of <0.001. There were 73 (81.1%) patients with low EUTO score achieved MMR and 26 (43.3%) patients with high EUTO score achieved MMR with p value of <0.001. There were 56 (80.0%) patients with low ELTS score achieved MMR, 40 (64.5%) patients with intermediate ELTS score achieved MMR and 03 (16.7%) patients with high ELTS score achieved MMR with p-value of <0.001. Conclusion: All scoring system such as Sokal, Hasford, AUTOS and ELTS are good in predicting the MMR in patients of CLM in chronic phase.